Achievements in Applications of Antioxidants and Bioactive Compounds in Food: From Agriculture to Health Benefits - Mia Kurek; Frédéric Debeaufort; Andrée Voilley (Antioxidants, 2024)
Natural foods and food components are becoming increasingly popular worldwide because people are concerned about eating healthy diets [...]